2014
DOI: 10.1186/1743-0003-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Tibialis Anterior muscle coherence during controlled voluntary activation in patients with spinal cord injury: diagnostic potential for muscle strength, gait and spasticity

Abstract: BackgroundCoherence estimation has been used as an indirect measure of voluntary neurocontrol of residual motor activity following spinal cord injury (SCI). Here intramuscular Tibialis Anterior (TA) coherence estimation was performed within specific frequency bands for the 10-60 Hz bandwidth during controlled ankle dorsiflexion in subjects with incomplete SCI with and without spasticity.MethodsIn the first cohort study 15 non-injured and 14 motor incomplete SCI subjects were recruited to evaluate TA coherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 68 publications
(118 reference statements)
4
34
1
Order By: Relevance
“…It would be interesting to test whether changes in IMC become substantiated and robust in longer term motor adaptation protocols and follow the “savings” measured in follow-up adaptation sessions on future days/weeks (Haith et al, 2015; Huberdeau et al, 2015). Evidence of high frequency activity may give crucial physiological insight into mechanisms of functional recovery and, following the examples found in the literature (Nishimura et al, 2009; Kisiel-Sajewicz et al, 2011; Fisher et al, 2012; Bravo-Esteban et al, 2014), we suggest high frequency IMC (40–100 Hz) should be further investigated in long term neurological conditions such as stroke.…”
Section: Discussionsupporting
confidence: 76%
“…It would be interesting to test whether changes in IMC become substantiated and robust in longer term motor adaptation protocols and follow the “savings” measured in follow-up adaptation sessions on future days/weeks (Haith et al, 2015; Huberdeau et al, 2015). Evidence of high frequency activity may give crucial physiological insight into mechanisms of functional recovery and, following the examples found in the literature (Nishimura et al, 2009; Kisiel-Sajewicz et al, 2011; Fisher et al, 2012; Bravo-Esteban et al, 2014), we suggest high frequency IMC (40–100 Hz) should be further investigated in long term neurological conditions such as stroke.…”
Section: Discussionsupporting
confidence: 76%
“…56 Imaging and electrophysiological measures associated with walking capacity In recent years, there has been growing interest in identifying electrophysiological and radiographical biomarkers that can predict locomotor outcomes. 60,144,145 Recent evidence from studies of TMS 146 and EMG coherence 60,144 have provided additional support for the importance of corticospinal pathways in human walking. More generally, there is some evidence that magnetic resonance imaging (MRI)-based measures are correlated with impairment.…”
Section: Variables Associated With Walking Functionmentioning
confidence: 99%
“…Moreover, we have recently demonstrated low intramuscular TA muscle coherence in subjects with the SCI spasticity syndrome, suggesting that this motor disorder is related to a dysfunction of descending motor drive. 36 We have also shown that exaggerated lower limb flexor reflex activity evoked in patients with incomplete SCI correlates with poor residual gait function. 16 However, it is also possible that abnormal CR activity after SCI may be associated with recovery of motor or locomotor function after injury.…”
Section: Discussionmentioning
confidence: 95%
“…29,31 Adoption of clinically relevant outcome measures, such as the Spinal Cord Assessment Tool for Spastic reflexes (SCATS), which provides a better evaluation of evoked flexor reflex activity, should also be evaluated. 16,36,67 Several experimental aspects of the reflex testing technique remain to be addressed, such as identifying correctly CR thresholds and normalising EMG data across experimental groups. We defined TA CR reflex threshold in part on the subjective assessment of the stimulus being innocuous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation